In vivo amyloid and tau metabolism in human brain tissue - Aslanyan, Aram; Mukherjee, Soumya; Dulewicz, Maciej; Coyle, Reid; He, Yingxin; Sato, Chihiro; Ghoshal, Nupur; Ge, Junyue; Moncur, Eleanor; Koutarapu, Srinivas; Camporesi, Elena; Thorne, Lewis; et al. (Alzheimer's & dementia, 2024)
Background Knowledge of the chemical composition of amyloid plaques and tau tangles at the earlier stages of Alzheimer’s disease (AD) pathology is sparse. This is due to limited access to human brain during life and at the earlier stages of AD pathophysiology and technical limitations in quantifying amyloid and tau species at a subcellular level. Understanding the chemical composition of plaques and tangles, how rapidly they grow and what factors drive growth is important for developing and refining therapeutics. We access in vivo cortical brain biopsy samples from individuals undergoing surgery, aiming to provide detailed characterisation of pathology with spatial and temporal resolution. Method We collected in vivo brain biopsies with matched ventricular and lumbar cerebrospinal fluid samples from individuals with suspected Normal Pressure Hydrocephalus (NPH) undergoing ventriculoperitoneal shunt surgery. All participants were labelled with intravenous 13C6 Leucine as per Stable Isotope Labelling Kinetics protocol. We used immunohistochemistry, immunoprecipitation‐mass spectrometry (IP‐MS) and Matrix Assisted Laser Desorption Ionization (MALDI) mass spectrometry‐based imaging (MSI) to characterise amyloid and tau and their common post‐translational modifications. We calculate the tracer‐to‐tracee ratio of labelled to unlabelled amyloid and tau to determine rate of pathological accumulation of these proteins. Using a 2‐compartment model we establish the half‐life of tau in brain tissue. Result We collected cortical brain biopsies from individuals with suspected NPH (n = 6), labelled between 4.25 hours to 133 days prior to surgery; 4 out of 6 individuals had amyloid plaques (range 1‐25 plaques/mm2). These individuals had mild cognitive impairment. Cored plaques showed characteristic localization of Aβ1‐40 and Aβ 3pE‐40 in the core while x‐42 species including 1‐42, 4‐42 and 3pE‐42 showed a more homogenous distribution across both plaque core and diffuse/immature plaque periphery (Figure 1, 2). We did not detect incorporation of labelled amyloid in any subject using IP‐MS or MALDI. We detected labelled tau in brain homogenate as early as 4.25 hours after label administration. The half‐life of tau in human brain was calculated to be 26.85 days. Conclusion Our study provides the first detailed chemical characterisation of AD pathology in living human brain giving insights into plaque composition, age and tau dynamics.